The legal position of waqf lands in Malaysia - Syed Abdul Kader, Sharifah Zubaidah (IIUM Press, 2017)
Malaysia is a federation consisting of 13 states and 3 federal territories. In respect of the states, each State Islamic Religious Council (SIRC) is declared by the law to be the ‘sole trustee’ of all waqf, whether general or specific waqf, in such state. Each SIRC has an administrative framework for waqf management consisting of their experts and officials to carry out the due administration of the waqf property for the benefit of the beneficiaries named in the waqf. If no beneficiaries are stated, this will be determined by the Islamic jurists based on the injunctions of the Qur'an and traditions of the Prophet Muhammad (SAW)